Halonium Catalysis: An Underutilized and Underexplored Catalytic Concept in Olefin Functionalizations - Gembreska, Nathan R.; Vogel, Alexander K.; Ziegelmeyer, Elizabeth C.; Cheng, Eric; Wu, Fan; Roberts, Leo P.; Vesoulis, Megan M.; Li, Wei (Synlett, 2020)
Iodonium catalysis is described here to accomplish an intermolecular olefin oxyamination reaction. Urea is used as the O- and N-source to add across both activated and unactivated alkenes in a regioselective manner. Mechanistic studies confirm the presence of an iodonium intermediate.1 Introduction2 Hypothesis3 Optimizations and Scope4 Mechanistic Probes5 Future Outlook
Keywords: iodonium catalysis; olefin oxyamination; regioselective; N-heterocycles; oxazolines; aminooxygenation